The ADD/ADHD checklist : - Rief, Sandra F. (John Wiley & Sons, Inc., 1998)
Written by a nationally known educator with two decades of experience in working with ADD/ADHD students. For fast, reliable information about attention deficit disorder, parents and teachers need only to refer to The ADD/ADHD Checklist. This unique resource is packed with up-to-date facts, findings, and proven strategies and techniques for understanding and helping children and adolescents with attention deficit problems and hyperactivity-- all in a handy list format.